Experiências X teologias (macro)ecumênicas. Uma articulação necessária - Júnior, Francisco de Aquino (Revista eclesiástica brasileira, 2005)
There is a close and constitutive relationship between the (macro)ecumenical praxis and its theory: every praxis carries with it a more or less conscious, more or less elaborated, theory; and every theory arises from a praxis (real or hypothetical) and refers to it. The respect for this relationship is an essential condition both for the strengthening and deepening of the (macro)ecumenical praxis and for the creative productiveness of the (macro)ecumenical theology. Both realities, praxis and theology, find in the poor and in their process of liberation the appropriate locus and the ultimate criterion of realization and verification.